Evolution of the Southwestern Angolan Margin: episodic burial and exhumation is more realistic than long-term denudation - Silva, Bruno V. da; Glasmacher, Ulrich A. (International journal of earth sciences, 2019)
There are two main points of view regarding how continental margins evolve. The first one argues that the present-day margins have been developed by long-term denudation since a major exhumation episode, probably driven by rifting or another relevant tectonic event. The second one argues that continental margins underwent alternating burial and exhumation episodes related to crustal tectonic and surface uplift and subsidence. To demonstrate that the proximal domain of the southwestern Angolan margin has evolved in a polycyclic pattern, we present a review of geological and thermochronological information and integrate it with new combined apatite fission-track and (U-Th)/He data from Early Cretaceous volcanic and Precambrian basement samples. We also provide hypotheses on the possible mechanisms able to support the vertical crustal movements of this margin segment, which are also discussed based on some modern rifting models proposed for Central South Atlantic. The central apatite fission-track ages range from 120.6 ± 8.9 to 272.9 ± 21.6 Ma, with the mean track lengths of approximately 12 µm. The single-grain apatite (U-Th)/He ages vary between 52.2 ± 1 and 177.2 ± 2.6 Ma. The integration of the thermochronological data set with published geological constraints supports the following time-temperature evolution: (1) heating since the Carboniferous-Permian, (2) cooling onset in the Early Jurassic, (3) heating onset in the Early Cretaceous, (4) cooling onset in the Mid- to Late Cretaceous, (5) heating onset in the Late Cretaceous, and (6) cooling onset in the Oligocene-Miocene. The thermochronological data and the geological constraints, support that the proximal domain of the southwestern Angolan margin was covered in the past by pre-, syn-, and post-rift sediments, which were eroded during succeeding exhumation events. For this margin segment, we show that a development based on long-term denudation is less realistic than one based on burial and exhumation episodes during the last 130 Myr.